2019
DOI: 10.1007/s10880-019-09662-y
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Glycemic Control in Adolescents with Type 1 Diabetes: The Moderating Role of Age, Gender, and Family Support

Abstract: Adherence and glycemic control usually decrease during adolescence and family relationships influence diabetes outcomes. This study analyzed the interaction effect of adolescents' family support, age, and gender in the relationship between adherence and glycemic control in adolescents with Type 1 Diabetes. The sample included 100 adolescents with Type 1 Diabetes and one of their parents during a routine endocrinology appointment. Adolescents answered the Self-Care Inventory-Revised, the Diabetes Family Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
(65 reference statements)
1
26
1
3
Order By: Relevance
“…According to Baumer et al preplanned outpatient appointments were less likely to have been attended if a child did not live with both parents (78.8% vs. 83.7%, p < 0.001), indicating temporal constraints of single parents 35 . Other explanatory approaches may include difficulties in providing, supervising and monitoring diabetes management (i.e., regarding the SMBG frequency, meals and snacks) 20,36 ; a diabetes caregiver other than the mother 37 ; health literacy 38 ; prevalence of life stressors 36 ; and family dynamics, such as cohesion, support, and conflict 20,39 …”
Section: Discussionmentioning
confidence: 99%
“…According to Baumer et al preplanned outpatient appointments were less likely to have been attended if a child did not live with both parents (78.8% vs. 83.7%, p < 0.001), indicating temporal constraints of single parents 35 . Other explanatory approaches may include difficulties in providing, supervising and monitoring diabetes management (i.e., regarding the SMBG frequency, meals and snacks) 20,36 ; a diabetes caregiver other than the mother 37 ; health literacy 38 ; prevalence of life stressors 36 ; and family dynamics, such as cohesion, support, and conflict 20,39 …”
Section: Discussionmentioning
confidence: 99%
“…Non-adherence in adolescents is said to be significantly higher than in younger children due to neurological changes as well as emotional and social challenges. [9][10][11] It is suggested that the late maturation of the prefrontal cortex conflicts with the requested action planning and risk control needed to act responsibly. 12 Non-adherence is likely to correlate both with the occurrence of rejections and the formation of dnDSA.…”
Section: Introductionmentioning
confidence: 99%
“…While every stage of development has its own tasks and characteristics, adolescence is particularly challenging. Non‐adherence in adolescents is said to be significantly higher than in younger children due to neurological changes as well as emotional and social challenges 9‐11 …”
Section: Introductionmentioning
confidence: 99%
“…The difference in engagement in treatment between males and females might influence glycemic stability. In addition, various factors may affect engagement in diabetes care, such as social support and depression (Almeida et al, 2019; Krass et al, 2015; Shrestha et al, 2013). Although the included studies did not clearly describe whether those factors were collected at recruitment, these issues could not have been identified in the meta‐analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Women tend to be more sensitive to symptoms of illness and more frequently seek care than men (Regitz-Zagrosek, 2012). Previous studies found that male populations with T1D had passive attitudes and low adherence to treatments for glycemic control (Almeida et al, 2019;Fitzgerald et al, 1995). The difference in engagement in treatment between males and females might influence glycemic stability.…”
Section: F I G U R E 3 (Continued)mentioning
confidence: 97%